Body composition in students physical education and sport: cross-sectional pilot study - Ratko Pavlović (Здоров’я, спорт, реабілітація, 2022)
Purpose: Young people who study physical education and sport are a priori regarded as having proper body structure and body composition. It is widely presumed that young who study physical education at one of several national universities of physical education (East Sarajevo) could be characterized with proper physique and body composition. Aim of the current study was to assess and analyze the body composition of a male students Physical Education and Sport, University East Sarajevo, by bioelectric impedance analysis and determine the significance of inter correlation coefficients.